Climate Change Effects on Grapevine Physiology and Biochemistry: Benefits and Challenges of High Altitude as an Adaptation Strategy - Arias, Leonardo A.; Berli, Federico; Fontana, Ariel; Bottini, Rubén; Piccoli, Patricia (Frontiers in Plant Science, 2022)
Grapevine berry quality for winemaking depends on complex and dynamic relationships between the plant and the environment. Winemakers around the world are demanding a better understanding of the factors that influence berry growth and development. In the last decades, an increment in air temperature, CO2 concentration and dryness occurred in wine-producing regions, affecting the physiology and the biochemistry of grapevines, and by consequence the berries quality. The scientific community mostly agrees in a further raise as a result of climate change during the rest of the century. As a consequence, areas most suitable for viticulture are likely to shift into higher altitudes where shortwave radiation increases. High-altitude can be defined as the minimum altitude at which the grapevine growth and development are differentially affected. This fact indefectibly affect wine since a reduction in fruit yield is directly associated with better quality of berries because of increased amounts of secondary metabolites. At these high-altitudes, the environments are characterized by high thermal amplitudes and great solar radiations, especially ultraviolet-B (UV-B). This review summarizes the environmental contribution on the grapevine physiology and wine composition, to a better understanding for the future applicability of high altitude in climate change scenarios.